Assessing the public understanding of democracy through conjoint analysis - Seki, Katsunori (Frontiers in Political Science, 2023)
Global support for democracy is puzzling in the time of alleged backlash toward democracy. Building on recent studies on democratic support that take into consideration heterogeneity in subjective perceptions of democracy, I conduct a conjoint analysis and examine trade-offs among various democratic values that citizens might face when they conceive of democracy. Using an original dataset of 2,206 respondents sampled from Japanese adult population, I find that the procedural view of democracy plays the most important role when Japanese people on average evaluate a country's democracy level. More specifically, in their view, a lack of free and fair elections and disenfranchisement of certain groups in society are more detrimental to democracy than a shortage of checks and balances, economic growth, and social welfare. At the same time, the analysis also shows that factors representing the minoritarian view and the substantive view of democracy play an undeniable role in citizens' democracy evaluations, which further confirms discrepancies between how students of democratization conceptualize and how ordinary people conceive of democracy today.